2014
DOI: 10.1158/1541-7786.mcr-14-0049
|View full text |Cite
|
Sign up to set email alerts
|

ID1 Promotes Breast Cancer Metastasis by S100A9 Regulation

Abstract: Metastasis is a major factor responsible for mortality in breast cancer patients. Inhibitor of DNA binding 1 (Id1) has been shown to play an important role in cell differentiation, tumor angiogenesis, cell invasion and metastasis. Despite the data establishing Id1 as a critical factor for lung metastasis in breast cancer, the pathways and molecular mechanisms of Id1 functions in metastasis remains to be defined. Here we show that Id1 interacts with TFAP2A to suppress S100A9 expression. We show that expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 49 publications
(55 reference statements)
1
27
0
2
Order By: Relevance
“…50 However, the mechanism by which ID1 and ID3 induce metastasis is not clearly understood. 53,54 Given the TGF-b signature data presented above, we sought to determine if ID1 and ID3 data alone could be used as an independent biomarker indicative of TGF-b activation in MSL/CL subtype of breast cancer. Using UNC855 dataset, we show that MSL/CL highly express ID1 and ID3 as an independent gene expression signature ( Fig.…”
Section: Tgf-b Signature Is Highly Expressed In Msl/cl Tnbc and Is Asmentioning
confidence: 99%
“…50 However, the mechanism by which ID1 and ID3 induce metastasis is not clearly understood. 53,54 Given the TGF-b signature data presented above, we sought to determine if ID1 and ID3 data alone could be used as an independent biomarker indicative of TGF-b activation in MSL/CL subtype of breast cancer. Using UNC855 dataset, we show that MSL/CL highly express ID1 and ID3 as an independent gene expression signature ( Fig.…”
Section: Tgf-b Signature Is Highly Expressed In Msl/cl Tnbc and Is Asmentioning
confidence: 99%
“…Id1 interacts with TFAP2A to suppress S100A9 expression. Migratory, invasive phenotypes in vitro and metastasis in vivo induced by Id1 expression can be rescued by reestablishment of S100A9 expression [55]. Id1 gene expression was also correlated with EMT-associated genes including, VIM, SNAI1, SNAI2, and TWIST1 [56].…”
Section: Breast Cancermentioning
confidence: 93%
“…Therefore, a positive correlation between ID1 and S100A9, and S100A8/9 would be expected. However, there is some controversy regarding this relation, as it has also been shown that ID1 downregulates S100A9 in breast cancer and promotes formation of metastasis [25]. Here, we aim to further unravel the relation between ID1 and downstream regulators such as S100A8/9 and S100A9, and investigate whether ID1 may, indeed, be centrally involved in the biology of suppressive myeloid cells.…”
Section: Introductionmentioning
confidence: 98%